Disentangling the evolutionary and biogeographical history of the freshwater fish trematode genus Creptotrema (Digenea: Allocreadiidae) using an integrative taxonomy approach: the case of Creptotrema agonostomi in Middle American mountain mullets. (15th July 2020) - Pérez-Ponce de León, G.; Sereno-Uribe, A.L.; García-Varela, M.; Mendoza-Garfias, B.; Hernández-Mena, D.I.; Pinacho-Pinacho, C.D.; Choudhury, A.
Abstract: Species of the allocreadiid genus Creptotrema are parasites of freshwater fishes in the Americas. Species in the genus possess one pair of muscular oral lobes on the oral sucker. Currently, the genus contains eight species, six distributed in South America, one in Middle America and one in North America. Genetic data are only available for the North American species, Creptotrema funduli, a parasite of fundulids originally described from Oneida Lake, New York State. In this study, we obtained 28S ribosomal DNA sequences of trematodes morphologically similar to Creptotrema agonostomi from the mountain mullet, Dajaus monticola, across a wide geographical range in Middle America. Our molecular phylogenetic analyses showed that (1) the genus Creptotrema, as currently conceived, is not monophyletic; (2) the allocreadiids in mountain mullets should be re-allocated in the genus Pseudoparacreptotrema ; and (3) the allocreadiid trematodes from D. monticola across Middle America represent four morphologically similar species, three of which can be distinguished genetically. These three new species are described herein using an integrative taxonomy approach. We contend that accurate estimates of species diversity and phylogenetic relationships among allocreadiids, and most likely other species of trematodes, necessarily require an integrative taxonomy approach that should consider at least DNA sequences and scanning electron microscopy.